Employees of Civil Aviation administrative and legal characteristics - Олійник, Олег Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article deals with the administrative and legal characteristics of employees in civil aviation. We analyze the normative and doctrinal understanding of the categories of «employee» and «administrative and legal status». Administrative and legal status of aviation personnel, its structure and properties are explored. Particular attention is focused on the properties of the status of civil servants. It’s mentioned in the article that according to the legislation civil aviation includes aviation that is used for the air transportation and aviations works’ needs of economics and citizens and also for the performing private flights. All these tasks are done by civil aviation staff or aviation personnel. In accordance with Air code of Ukraine aviation personnel include persons that got specific professional preparation, have certain document and carry out flight operation, aircraft maintenance, air traffic management, technical operation of terrestrial communications, navigation, surveillance. It’s concluded in the paper that state aviation personnel has a special place and role in the system of aviation subjects.